Identification of the Antibacterial Chemical Constituents of Amorpha fruticosa L. by A Modified High-Throughput Screening Method - Yun-Peng, Diao; Qing-Gao, Li; Kun, Li; Fei, Wang; Jian-Kui, Zhang; Liang, Xu; Shan-Shan, Huang; Hou-Li, Zhang; Ting-Guo, Kang (Asian Journal of Chemistry, 2011)
An antibacterial high throughput screening (HTS) method is developed for the Amorpha fruticosa L. fruit extracts, which were tested against methicillin-resistant Staphylococcus aureus (MRSA). The chloroform extract was separated into 80 fractions via preparative high performance liquid chromatography (HPLC). The optimal fractions and tephrosin were tested against methicillinresistant Staphylococcus aureus using high throughput screening method and the antibacterial activity of those selected bioactive fractions was further confirmed by MIC method. Tephrosin exhibited more excellent inhibition ratio than optimal fraction for methicillin-resistant Staphylococcus aureus. Amorpha fruticosa L. exhibited the strongest antibacterial activity and thus the optimal fraction was obtained.